Introduction Rukun of Islam Through Printable Media in Group A Early Childhood Education Lakasombu - Yusniati Yusniati; Henny Henny; Kadar Risman (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
The basic teachings of Islam are the pillars of Islam. As Muslims, we are all obliged to obey God's teachings, especially the teachings of Islam. Reciting the shahada, performing the five daily prayers, paying zakat, fasting during Ramadan and performing the Hajj are the five pillars of Islam. The aim of this research is to find out how group A at PAUD Lakasombu uses print media to learn the basic principles of Islam. Descriptive qualitative research is the method of choice for examining existing problems and practical work practices. The purpose of this qualitative descriptive research is to provide an overview of the research process. This research uses group A environment in PAUD Lakasombu as the unit of analysis. Research findings show that the use of printed materials to introduce Islamic teachings has succeeded in positively influencing children's development. The pillars of Islam will of course be introduced to children from an early age, equipping them with basic knowledge and encouragement to develop skills, independence and Islamic discipline.